Efeitos da elasticidade e blindagem eletrostática nas interações Dna- ligantes estudados via a técnica de pinçamento óptico - Patrícia Santos Alves (2016)
We have studied the changes on the mechanical properties of two different types of DNA-ligand complexes. Single molecule stretching experiments were performed by using the optical tweezers technique, from which the contour and persistence lengths of the complexes can be promptly extracted. The rst DNA ligand studied was the neutral-cyclodextrin. From the persistence length behavior as a function of the cyclodextrin concentration, we concluded that a cooperative process occurs for this interaction, determining the relevant physicochemical parameters. The results indicate that the balance between attractive and repulsive forces is a mediator for the cooperativity observedin this process. We also studied the interaction between the protein lysozyme and the DNA molecule performing the same type of stretching experiments at different sodium concentrations in the buffer solution. The results suggest that the observed non-monotonic behavior of the persistence length of the complexes in this case is due to competition between two factors: (a) the increase of the eective diameter of theDNA-lysozyme complexes, which increases its bending rigidity, and (b) the decrease of the negative charge density of the phosphate backbone, which reduces the persistence length. Furthermore, the experimental results indicate a change of the lysozyme conformation bound along the double-helix as we change the sodium concentration in the buffer.